Proceedings of the Ocean Drilling Program 1992
DOI: 10.2973/odp.proc.sr.127128.150.1992
|View full text |Cite
|
Sign up to set email alerts
|

Miocene Pollen Stratigraphy of Leg 127 in the Japan Sea and Comparison with the Standard Neogene Pollen Floras of Northeast Japan

Abstract: Pollen floras were obtained from Miocene sediments recovered at four sites drilled during Ocean Drilling Program Leg 127. The local pollen floras of each site were correlated to the standard pollen zones of northeast Japan by using the concept of the essential members for each pollen zone. At Site 797, the complete floral range was obtained for recognition of the NP2 zone and the pollen components of the NP1 zone were also clarified continuously. The ages of the boundaries between pollen zones NP4/NP3, NP3/NP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 3 publications
2
12
0
Order By: Relevance
“…Investigations of the Oligocene Brandon lignite showed that the diagenesis of terpenoids is controlled by microbial activities rather than by thermal stress (Stout, 1992). Palynology from units II, III and IV indicates a vegetation type typically occurring in South East Asia during Oligocene and Neogene (Yamanoi 1992;Wang et al 2001;Yagashita et al 2003). Lignites within units III and IV contain pollen and spore floras that are very similar to the clastic rocks in these units.…”
Section: Palynologymentioning
confidence: 99%
“…Investigations of the Oligocene Brandon lignite showed that the diagenesis of terpenoids is controlled by microbial activities rather than by thermal stress (Stout, 1992). Palynology from units II, III and IV indicates a vegetation type typically occurring in South East Asia during Oligocene and Neogene (Yamanoi 1992;Wang et al 2001;Yagashita et al 2003). Lignites within units III and IV contain pollen and spore floras that are very similar to the clastic rocks in these units.…”
Section: Palynologymentioning
confidence: 99%
“…Biostratigraphic work has been conducted on samples from the Hole of Ocean Drilling Program Legs 127 and 128 drilled in the Yamato Basin of East Sea (Burckle et al . 1992; Nomura 1992; Rahman 1992; Yamanoi 1992). The oldest marine sediment is late Early Miocene in the basin, based on the calcareous nannofossil Helicosphaera ampliaperta Zone (15.7–18.4 Ma) in the Holes 797B and 797C, Leg 127 (Rahman 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The Daijima‐type Flora represents an oceanic warm‐to‐temperate climate; this flora is believed to have replaced the Aniai‐type Flora, a cool‐to‐temperate inland flora (Huzioka 1963), as warm seawater flowed into the back‐arc basin of the Japan Arc (Huzioka 1972; Koizumi 1988). The estimated age of the first occurrence of the Daijima‐type Flora ranges from ca 22 Ma (Kano & Yanagisawa 1989) to 18 Ma (Uemura 1989; Yamanoi 1992). This uncertainty is perhaps because a short‐term return to the Aniai‐type Flora from the Daijima‐type Flora recurred due to global cooling during the periods between 19 and 18 Ma and between 16 and 15 Ma (Kano & Yanagisawa 1989).…”
Section: Stratigraphic Frameworkmentioning
confidence: 99%